Understanding land idling as a strategic behaviour: A real options approach - Khalid, Haniza (2013)
One possible explanation for land idling in a rapidly transforming economy can be found by looking at the value of the option to wait and hysteresis behaviour in the land market. If investors assume that the drop is temporary and that its long term prospects outweigh current holding losses, the market will observe some form of a zone of inactivity i.e., no selling and no additional buying. The fact that landowners elect to keep their valuable land underdeveloped for prolonged periods of time suggests that idled land is more flexible and valuable than what the current market price suggests. If the revenue from farming is insufficient to sustain the activity, land is left idle; although this operational decision is open to continuous revision. The numerical example shown in the paper shows that price of land can be substantially bolstered by the option to wait embedded in land.